Impact of risk management culture on supply chain resilience: An empirical study from Indian manufacturing industry. (April 2020) - Kumar, Siva; Anbanandam, Ramesh
The frequency of supply chain disruptions is growing. The recent supply chain disruptions and their costs emphasize the need for resilient supply chains. Therefore, the main purpose of this study is to investigate interactions between critical antecedents of supply chain resilience including risk management culture, supply chain connectivity, visibility, collaboration, agility, their impact on supply chain resilience, and finally on firm performance. Using the same antecedents and literature support, an empirical model has been proposed. The proposed model has been tested using rigorous statistical analysis such as reliability, convergent, and discriminant validity tests. Partial least squares-structural equation modelling has been used to validate the proposed model and the interdependencies between the critical antecedents. An important finding of this research is that organizations, using the proposed model, can develop and improve supply chain resilience capability by establishing the risk management culture through improving the risk awareness among employees and conducting periodic risk assessment exercises. In addition, the study suggests that organizations trying to achieve supply chain resilience must develop sufficient supply chain connectivity and visibility through adopting information and communications technologies and visibility tools for quick response and recovery from supply chain disruptions. Data collected from the Indian manufacturing sector are used to validate the model. The holistic view presented by the proposed model describes the inter-relationships between critical antecedents to achieve supply chain resilience. Concluding remarks and future research avenues have been presented.